SURVEI KANDUNGAN RESIDU OKSITETRASIKLIN PADA HATI AYAM YANG DIJUAL DI PASAR TRADISIONAL KECAMATAN BANYUMANIK KOTA SEMARANG - sheila choirunnisa; M. Arie Wuryanto; Nissa Kusariana; Lintang Dian Saraswati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
OTC is commonly used in medicine and is one of the main antibiotics used in zootech-nical and veterinary practices as feed additive to ensure wellness of farmed. Antibiotic commonly used in livestock industry to prevent disease amd as feed additive. However, the use of antibiotics can cause residues in livestock products that produced by antibiotics used not in accordance with the rules. The purpose of this study is to determine the description of the presence of oxytetracycline antibiotic residues in chicken liver sold in the traditional market of Banyumanik District, Semarang City. The type of this study used is descriptive study. The sample taken is chicken liver which is sold in Rasamala and Damar traditional markets while sample testing is carried out in Boyolali BALIVET laboratory. The number of samples issued amounted to 23 samples, namely 21 samples of liver broiler chicken and 2 samples of kampong chicken. The results showed that all samples of chicken liver did not contain oxytetracycline residues. The trial of antibiotic residue uses Bioassay method to know residue of oxytetracycline in the sample. The result showed that chicken liver which sold in Rasamala and Damar traditional market is secure from the presence of oxytetracycline antibiotic residue.